Weak Type Inequalities for Fractional Integral Operators on Generalized Non-Homogeneous Morrey Spaces (Analysis in Theory and Applications, 2012)
We obtain weak type $(1,q)$ inequalities for fractional integral operators on generalized non-homogeneous Morrey spaces. The proofs use some properties of maximal operators. Our results are closely related to the strong type inequalities in [13, 14, 15].
Keywords: weak type inequality fractional integral operator; (generalized) non-homogeneous Morrey space.